2017
DOI: 10.1002/pi.5488
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic diblock and crosslinked copolymers synthesized via metal‐free atom transfer radical polymerization

Abstract: The use of metal-free atom transfer radical polymerization (MF-ATRP) was explored for the formation of diverse macromolecular structures to assess the versatility of this advanced polymerization process. In MF-ATRP using an organic photocatalyst, 10-phenylphenothiazine, the influences of various monomers, initiators and solvents were examined, showing that molecular weight and polydispersity could be tailored through appropriate selection of each component. Using this modern polymerization technology, metal-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, changes in monomer structure can also be expected to impact other polymerization conditions such as In addition to these alkane-functionalized methacrylates, a number of methacrylates with heteroatom-containing aliphatic groups have been polymerized successfully. These monomers include methacrylic acid, 170 2-hydroxyethyl methacrylate, 87 diethylene glycol methyl ether methacrylate, 155 poly(ethylene glycol) methacrylate, 97,122 glycidyl methacrylate, 171 and diethylamino ethyl methacrylate. 171 A number of aromatic monomers have also been polymerized, including benzyl methacrylate 33,35 and furfuryl methacrylate, 66,172 although not as extensively as aliphatic methacrylates.…”
Section: Methacrylatesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, changes in monomer structure can also be expected to impact other polymerization conditions such as In addition to these alkane-functionalized methacrylates, a number of methacrylates with heteroatom-containing aliphatic groups have been polymerized successfully. These monomers include methacrylic acid, 170 2-hydroxyethyl methacrylate, 87 diethylene glycol methyl ether methacrylate, 155 poly(ethylene glycol) methacrylate, 97,122 glycidyl methacrylate, 171 and diethylamino ethyl methacrylate. 171 A number of aromatic monomers have also been polymerized, including benzyl methacrylate 33,35 and furfuryl methacrylate, 66,172 although not as extensively as aliphatic methacrylates.…”
Section: Methacrylatesmentioning
confidence: 99%
“…These monomers include methacrylic acid, 170 2-hydroxyethyl methacrylate, 87 diethylene glycol methyl ether methacrylate, 155 poly(ethylene glycol) methacrylate, 97,122 glycidyl methacrylate, 171 and diethylamino ethyl methacrylate. 171 A number of aromatic monomers have also been polymerized, including benzyl methacrylate 33,35 and furfuryl methacrylate, 66,172 although not as extensively as aliphatic methacrylates.…”
Section: Methacrylatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of homopolymers and block copolymers by O‐ATRP is well‐known and has been explored by several authors. [ 112–114 ] Therefore, scientists often synthesize these types of polymers as part of more complex structures. The efforts to simplify the synthesis of block copolymers are notable.…”
Section: Polymer Architectures By O‐atrpmentioning
confidence: 99%
“…Amphiphilic block copolymer attracts considerable attention due to its self-assemble ability, and has been widely used in drug and gene delivery areas [ 162 , 163 , 164 , 165 ]. Son et al reported that an amphiphilic diblock copolymer could be prepared through metal-free ATRP by using Ph-PTZ as organic photocatalyst under the irradiation of LED light (380 nm) [ 166 ]. This method was also successfully applied to the polymerization of MMA, GMA, BA, 2-diethylaminoethyl methacrylate (DEAEMA), and allyl methacrylate (AMA).…”
Section: The Metal-free Catalyst Mediated Atrp Systemmentioning
confidence: 99%